Konsep Hutang Piutang dalam Ekonomi Islam : Kajian Qs. Al-Baqarah Ayat 282 dalam Perspektif Tafsir Al-Qur’an Al-Azhim Karya Ibnu Katsir - Samsidar; Syamsurianto; Achmad Abubakar; Halimah Basri; Muh. Azka Fazaka Rifa’i (VISA: Journal of Vision and Ideas, 2024)
Debt is a transaction in which two people voluntarily give money to another person and then return it to them in the same way. This study aims to determine how Ibnu Katsir views the concept of accounts payable and receivable from an Islamic economic perspective. Although we know that debts and receivables are permitted, Islam advises its followers to avoid debts as much as possible, regardless of whether they can afford to buy something with cash or not when they are in limited economic conditions. Because debt is always a heavy burden and threatens morality. Rasulullah saw. once refused to pray for the body of someone who owed a lot of debt to his family and did not have the means to pay it. As explained in the Koran, recording or writing is the first step in debt and receivable transactions. This research uses library research methods with an interpretive science approach using the tahlili method. The results of this research show that people who owe money are obliged to tell the clerk about the debt they admit because they are worried that there will be fraud against those who owe it. If it is a buying and selling transaction, it is permissible not to record or write down the transaction. Furthermore, there is a need for fair witnesses. In terms of testimony, Ibnu Katsir stated that being a witness is fardlu kifayah or not mandatory for the person concerned unless there is another person who can replace his position